PENGARUH BERBAGAI DOSIS PUPUK ORGANIK DAN JARAK TANAM TERHADAP HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) - Marwani; Idham; Nursalam (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2026)
This study aims to determine the growth and yield of peanut plants at the use of organic fertilizer doses with different spacing. This research was carried out in the village of Kota Rindau, Dolo District from November 2019 to February 2020. This research was conducted using a factorial randomized block design consisting of 2 factors, the first factor was the use of various doses of organic fertilizer, namely 10 tons.ha-1, 15 tons.ha-1, 20 tons.ha-1 and spacing of 30 cm x 30 cm, 30 cm x 35 cm and 30 cm x 40 cm, the treatment was repeated 3 times so that there were 27 experimental units. To get better seed yields, the use of higher doses of organic fertilizers requires more tenuous spacing. The application of 20 tons. ha-1 of organic fertilizer produced better results, indicated the number of pods was more, the percentage of empty pods was less and the weight of 100 seeds was more pithy. Spacing of 30 cm x 40 cm produced better results, indicated by the number of pods more, the percentage of empty pods is less and the weight of 100 seeds is more pithy.